Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/w10070853
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Models Combining EMD/EEMD and ARIMA for Long-Term Streamflow Forecasting

Abstract: Long-term streamflow forecast is of great significance for water resource application and management. However, accurate monthly streamflow forecasting is challenging due to its non-stationarity and uncertainty. Time series analysis methods have been proved to perform well in stationary time series forecasting, which can be derived from decomposition of the non-stationary sequence. As common decomposition methods in time domain, Empirical Mode Decomposition (EMD) and Ensemble Empirical Mode Decomposition (EEMD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 52 publications
(74 reference statements)
0
30
0
Order By: Relevance
“…Liu et al [64] implemented a hybrid method to predict wind speed, in which the wavelet transform was used to decompose the wind speed signal into two components and the approximated signal (one of two components) was modeled by a support vector machine. Zhi et al [65] selected empirical mode decomposition (EMD) as the decomposition method for the time series, and components with different features in the original hydrological time series were decomposed. Yaslan et al [66] predicted power load demand using a combined EMD and support vector regression (SVR) model.…”
Section: Combined Methodsmentioning
confidence: 99%
“…Liu et al [64] implemented a hybrid method to predict wind speed, in which the wavelet transform was used to decompose the wind speed signal into two components and the approximated signal (one of two components) was modeled by a support vector machine. Zhi et al [65] selected empirical mode decomposition (EMD) as the decomposition method for the time series, and components with different features in the original hydrological time series were decomposed. Yaslan et al [66] predicted power load demand using a combined EMD and support vector regression (SVR) model.…”
Section: Combined Methodsmentioning
confidence: 99%
“…The objective of EMD is to decompose the nonlinear and nonstationary data adaptively into number of oscillatory components called Intrinsic Mode Decomposition (IMF). A number of studies have been conducted combining the EMD with data driven models [15,[18][19][20][21]. Specifically in hydrology, EMD is used with ANN for wind speed and stream flow prediction [15,20].…”
Section: Introductionmentioning
confidence: 99%
“…Accurate prediction results in better decisions such as, flood and drought controls, the supply of drinking water, water resources management and physical-based models, data-driven models, and hybrid models (Chen et al, 2018). All these models have been widely used to predict rivers flow and other hydrologic analyses (Erdal & Karakurt, 2013;Hao et al, 2017;Chen et al, 2018;Darwen, 2018;Wang et al, 2018). Physicalbased models extract the inherent behaviors of hydrological variables by conceptualizing their physical process and characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…They took monthly streamflow data and concluded that application of ARIMA can be useful in generating precise prediction. However, the disadvantages of TS models are that the river inflow data must be linear which limits the application of these models (Wang et al, 2018). (Behzad et al, 2009) and many other non-linear problems (Wu & Lin, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation